Heparins are potent inhibitors of ectonucleotide pyrophosphatase/phospho-diesterase-1 (NPP1) – a promising target for the immunotherapy of cancer - Lopez, Vittoria; Schuh, H. J. Maximilian; Mirza, Salahuddin; Vaaßen, Victoria J.; Schmidt, Michael S.; Sylvester, Katharina; Idris, Riham M.; Renn, Christian; Schäkel, Laura; Pelletier, Julie; Sévigny, Jean; Naggi, Annamaria; et al. (Frontiers in Immunology, 2023)
Heparins, naturally occurring glycosaminoglycans, are widely used for thrombosis prevention. Upon application as anticoagulants in cancer patients, heparins were found to possess additional antitumor activities. Ectonucleotidases have recently been proposed as novel targets for cancer immunotherapy.In the present study, we discovered that heparin and its derivatives act as potent, selective, allosteric inhibitors of the poorly investigated ectonucleotidase NPP1 (nucleotide pyrophosphatase/phosphodiesterase-1, CD203a). Structure-activity relationships indicated that NPP1 inhibition could be separated from the compounds' antithrombotic effect. Moreover, unfractionated heparin (UFH) and different low molecular weight heparins (LMWHs) inhibited extracellular adenosine production by the NPP1-expressing glioma cell line U87 at therapeutically relevant concentrations. As a consequence, heparins inhibited the ability of U87 cell supernatants to induce CD4 + T cell differentiation into immunosuppressive Treg cells. Thus, NPP1 inhibition likely contributes to the anti-cancer effects of heparins, and their specific optimization may lead to improved therapeutics for the immunotherapy of cancer.